Stemphylium lycopersici and Stemphylium solani improved antioxidant system of soybean under chromate stress - Husna, Husna; Hussain, Anwar; Shah, Mohib; Hamayun, Muhammad; Iqbal, Amjad; Qadir, Muhammad; Asim, Syed; Lee, In-Jung (Frontiers in Microbiology, 2022)
Ecologists around the world are giving great attention to the metal pollution of agronomic soil. Recently, several techniques have been employed to remediate heavy metals, but the use of microorganisms is the most viable and ecofriendly. In the current study, the endophytic strains, Cp1 and Cp2 were isolated from sterilized 1-5 cm long root and leaf segments of Chlorophytum comosum using Hagem media. To get pure colonies, the strains were repeatedly cultured on potato dextrose agar (PDA) media. The strains Cp1 and CP2 were identified as Stemphylium lycopersici and Stemphylium solani based on ITS sequencing and neighbor joining (NJ) method. Both strains showed a growth promoting potential in soybean seedlings exposed to chromate (Cr) stress. Moreover, S. lycopersici and S. solani improved the IAA, flavonoids, phenolics, protein and proline contents, whereas lowered SA production in the seedlings. The selected endophytic fungal strains also promoted the antioxidant system of soybean seedlings through enhanced production of ascorbic acid oxidase (AAO), catalases (CAT), peroxidase and free radical scavenging enzymes. Both strains bio-transformed the toxic Cr-VI to less toxic Cr-III in the cultural filtrate as well as host plants. In fact, efficient uptake of Cr and its conversion by the isolated endophytic fungal strains could be used as a viable tool to remediate Cr contamination in agricultural soils.